2010
DOI: 10.1210/jc.2009-1919
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Profile and Urinary Albumin Excretion in Isolated Growth Hormone Deficiency

Abstract: Background: GH deficiency (GHD) is often associated with cardiovascular risk factors, including abdominal fat accumulation, hypercholesterolemia, and increased C-reactive protein. Despite the presence of these risk factors, adults with congenital lifetime isolated GHD (IGHD) due to an inactivating mutation in the GHRH receptor gene do not have premature atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
(20 reference statements)
2
21
0
1
Order By: Relevance
“…ADP could be a potential new target drug for curing fat metabolism disorders (Krakoff et al, 2003). This study demonstrated that ADP levels in adult GHD patients are higher than those in healthy individuals, which corresponds to the conclusion drawn by Oliveira et al (2010). Currently, there is little research on ADP levels in adult GHD patients owing to the small number of subjects, the absence of reference hypophysis hormone levels, and different methods.…”
Section: Discussionsupporting
confidence: 79%
“…ADP could be a potential new target drug for curing fat metabolism disorders (Krakoff et al, 2003). This study demonstrated that ADP levels in adult GHD patients are higher than those in healthy individuals, which corresponds to the conclusion drawn by Oliveira et al (2010). Currently, there is little research on ADP levels in adult GHD patients owing to the small number of subjects, the absence of reference hypophysis hormone levels, and different methods.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that a very low level of IGF-I might have a protective role, whereas a milder decrease (as seen in adult-onset GH deficiency) might be noxious (48). In addition, the increase in serum adiponectin (protein influenced by GH level) may contribute to such a beneficial outcome (52). They also exhibit normal urinary albumin excretion.…”
Section: Metabolic and Cardiovascular Consequencesmentioning
confidence: 99%
“…These features have been published in 42 different publications (2,19,22,25,27,29,30,31,32,33,36,37,38,40,41,44,45,46,47,48,49,50,51,52,53,54,56,57,61,62,63,64,66,67,68,74,75,76,77,78,79,80). We have used this experiment of nature to discover 'usual laws of nature' as suggested by William Harvey, and to understand some aspects of more common conditions such as short stature, insulin resistance, diabetes, atherosclerosis, osteoporosis, cancer and ultimately longevity.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the number of individuals with atherosclerosis plaques did not further increase with longer follow-up, but in one individual the plaque disappeared, showing that despite some conflicting data (19,20), it is possible not only to reduce vascular wall volume but also to decrease plaques' volume as shown with some lipid-lowering agents (21,22). This occurred despite atherogenic conditions, such as abdominal obesity, increased SBP, LDL, and CRP (8,9,10).…”
Section: Discussionmentioning
confidence: 68%
“…These individuals have very low serum GH and insulin-like growth factor 1 (IGF1), reduced fat-free mass, increased percentage of fat mass, total and LDL, CRP levels, systolic blood pressure (SBP), and waist:hip ratio. Despite these cardiovascular risk factors, they have no premature atherosclerosis, no insulin resistance, and normal longevity (7,8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%